Artes del cuerpo y pedagogías radicales - Greiner, Christine; Ferreira, Fabio; Souto, Luciano; Faúndez C., Tania (Teatro, 2022)
In 1999 we began a pedagogical experience in São Paulo, with the creation of the Artes do Corpo undergraduate course. More than a degree in dance or theatre, this course was designed to train artists, researchers and cultural managers interested in the intersections between dance, theatre and performance; and through dialogues with other areas of knowledge such as philosophy, science and politics. It is evident that all the experiences focused on dance, theatre and performance already necessarily work with the body. But not everyone conceives artistic language as a possibility to reinvent bodies and movements. An example of how this educational project has been opening different paths is that of the actor Thiago Cavalli, who decided to create Casa do Rio, in the interior of the Amazon, in the rural part of the jungle. This NGO has been working on different fronts, always thinking about pedagogy from the point of view of art. Part of the project: work with children, local artisans, memory of almost extinct communities and indigenous medicine. In the Colloquium we present this, among other experiences that were triggered by training in body arts and the alliances between these practices and life policies.